2016
DOI: 10.1093/ehjci/jew024
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension is associated with worse survival in hypertrophic cardiomyopathy

Abstract: Over one-third of adults evaluated in our referral HCM clinic demonstrated concomitant PH, and this was associated with increased mortality except in those with obstructive HCM who underwent SRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 34 publications
5
42
1
Order By: Relevance
“…6 A more recent study reported that pulmonary hypertension, as measured with Doppler echocardiography, predicted HCM-related death. 21 The present study reports, for the first time, that elevated RAP is associated with increased risk of death in HCM patients. The association remained significant after adjusting for possible confounding factors.…”
Section: Discussionsupporting
confidence: 49%
“…6 A more recent study reported that pulmonary hypertension, as measured with Doppler echocardiography, predicted HCM-related death. 21 The present study reports, for the first time, that elevated RAP is associated with increased risk of death in HCM patients. The association remained significant after adjusting for possible confounding factors.…”
Section: Discussionsupporting
confidence: 49%
“…4 On the other hand, we have the unique opportunity to report here the role of pulmonary hypertension in advanced heart failure with cardiopulmonary hemodynamics measured directly at cardiac catheterization. 13 The study group comprises a consecutive cohort of patients undergoing surgical septal myectomy (or alcohol septal ablation) to relieve outflow tract obstruction and mitigate heart failure symptoms, at a single HCM tertiary referral institution.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports characterizing pulmonary artery pressure dynamics in obstructive HCM patients have relied largely on estimates derived from Doppler echocardiography studies, and attributed adverse consequences (i.e., all-cause mortality) to pulmonary hypertension. 3,4 Therefore, in the present analysis we have re-visited clinical issues surrounding pulmonary hypertension in a unique cohort of HCM patients using hemodynamic data obtained at cardiac catheterization.…”
mentioning
confidence: 99%
“…Chest CT was not done as the radiation dose of the high resolutional CT which is needed for the proper evaluation of parenchymal lung disease expose the person to high radiation dose approaching 100 times and should be reserved for selective and proper diagnosis of cases like interstial fibrosis or patients with immunedeficiency [26]. In our study we excluded Hypertrophic obstructive cardiomyopathy (HOCM) cases as there is more evidences of associated pulmonary hypertension with HOCM which was found to be associated with increased mortality in HOCM patients [27]. Abnormal thyroid function whether thyroiditis or hyperthyroidism also excluded from the study as there is high association with the pulmonary hypertension which is reversed when the thyroid function returns to the normal [28].…”
Section: Discussionmentioning
confidence: 99%